Transactions on Edutainment VIII - Chang, Maiga; Zhang, Mingmin (Transactions on Edutainment, 2012)
This journal subline serves as a forum for stimulating and disseminating innovative research ideas, theories, emerging technologies, empirical investigations, state-of-the-art methods, and tools in all different genres of edutainment, such as game-based learning and serious games, interactive storytelling, virtual learning environments, VR-based education, and related fields. It covers aspects from educational and game theories, human-computer interaction, computer graphics, artificial intelligence, and systems design. This issue contains 10 outstanding contributions from the International Conference on E-Learning and Games, Edutainment 2011, as well as 14 regular papers which were partly selected from national conferences. The topics covered are game engine, using games to teach, identifying player emotion states, assessing the effects of educational games to multi-touch interaction, natural user interface, and virtual reality. Generally, the papers present a large number of examples of edutainment applications, giving more evidence on the high potential and impact of edutainment approaches.